Analisis Kemampuan Pemecahan Masalah pada Materi Sistem Koordinat Kartesius Ditinjau dari Perbedaan Pola Pikir Divergen dan Konvergen Siswa Kelas VIII SMP - Naba Nunun Lamhabaha; Sudi Prayitno; Muhammad Turmuzi; Syahrul Azmi (Griya Journal of Mathematics Education and Application, 2021)
This study aims to determine how the ability of mathematical problem solving in the Cartesian coordinate system material in terms of differences in divergent and convergent thinking patterns in class VIII students in semester 1 of SMP Negeri 1 Kediri in the 2019/2020 academic year. This research is a descriptive study using a quantitative approach. The instruments used in this study were the thinking character questionnaire instrument and the problem solving ability test instrument. The thinking character questionnaire instrument was used to select research samples that met the criteria for divergent thinking and convergent thinking. In this study, 11 students thought divergent and 12 students thought convergent. The problem-solving ability test instrument was used to determine the problem-solving ability of the research sample as measured by Polya's assessment guidelines, namely (1) understanding the questions, (2) planning solutions, (3) solving problems, and (4) checking. The results showed that there was no difference in the average score of problem-solving abilities between students with divergent and convergent thinking patterns, namely 66.19 and 66.73. The only difference lies in the steps each student takes. This shows that different mindsets do not affect a person's ability to solve a problem.